Analysis of Representation of Gender Ideology in Stylistic Layers of Personal Persian Elegies - Zahra Esmailiyan azari; Narges Oskouie; Hosein Dadashi (مطالعات زبانی و بلاغی)
The representation of gender ideology is to show the author's gender world (beliefs, customs and traditions, behavioral acts expected from both sexes, distribution of power between the two sexes) either from a position of agreement with the dominant discourse of the society or from a critical point of view in the text. The main objective of this research is the analysis of the representation of gender ideology in the stylistic layers of the personal elegies of Persian-speaking male and female poets. The representation of poet's individuality (self) in personal elegies makes it feasible to study author's identity, for instance in terms of gender. This study was conducted via a combined research method (descriptive-statistical-comparative analysis), employing layered stylistics as the theoretical basis. The following results were obtained from this research (in three lexical, syntactic and rhetorical layers). Symbols indicating submission and satisfaction, short and discrete sentences and emotional and sensory rhetorical devices are   used more often in the elegiac writing of female author to reflect the concepts of acceptance of fate, internalization of gender role and status, as well as oppression and inferiority, in line with the dominant discourse. The ideology represented in the personal elegies of male authors indicates authoritative protest and overbearing authoritarianism. Compared to women's emotional emotions that can be found in their declarative and emotional speech acts and short and discrete elegiac sentences, men have reflected more logical reflections with long continuous sentences, persuasive speech acts and more rhetorical tools.